Methylation Status of hMLH1 Gene in Colorectal Cancer Patients in Ethnic Population of Kashmir Valley - Dar, Mashooq A; Bhat, Showkat A; Ahmad Arif; Hilal Ahmad Wani; Khalid B Dar; Maqbool, Rouf; Anees, Suhail; Manzoor R Mir (International Journal of Medical Research, 2013)
Background: Colorectal cancer is commonly known as bowel cancer, its development and progression is dictated by chain of alterations in genes such as tumor suppressor genes, DNA repair genes, oncogenes and others. Method: The present work was a case control study aiming to ascertain the role of promoter methylation of CpG islands of hMLH1 gene in colorectal cancer patients among the Kashmiri population. DNA was extracted from all the samples and was modified using bisulphite modification kit. Methylation-specific polymerase chain reaction was used for the analysis of the promoter methylation status of hMLH1 gene. Results: The epigenetic analysis revealed that unlike other high risk regions, Kashmiri population has a different promoter methylation profile of hMLH1 gene as 67.5 % of the cases showed hMLH1 promoter methylation in comparison to 15 % of the normal cases which also showed promoter methylation of hMLH1 gene. The association of promoter methylation with colorectal cancer was found to be significant (P=0.0006). Occurrence of hMLH1 promoter methylation was found to be unequally distributed in males and females with more frequency in males than in females but the difference was not statistically significant (P=0.7635). Similarly, frequency of hMLH1 promoter methylation was found to be certainly higher in Stage III/IV (85.71%) compared to Stage I/ II (57.69%) but the difference was not statistically significant (P=0.0673). Conclusion: The results suggest that hMLH1 aberrant promoter methylation in Kashmiri population contributes to the process of carcinogenesis in colorectal cancer and is reportedly one of the commonest epigenetic changes in the development of colorectal cancer.